2014
DOI: 10.3892/mmr.2014.2231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arazyme on the lipopolysaccharide-induced inflammatory response in human endothelial cells

Abstract: Abstract. Arazyme is a novel extracellular metalloprotease secreted by Aranicola proteolyticus. Endothelial cells are involved in the pathogenesis of a number of inflammatory diseases, induce uncontrolled cell viability and express various inflammatory mediators, including cytokines, chemokines, adhesion molecules and reactive oxygen species (ROS). In the current study, human umbilical vein endothelilal cells (HUVECs) were used to investigate the anti-inflammatory effects of arazyme following lipopolysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…To determine whether chrysin inhibits inflammation, we performed RT-PCR and Western blotting to evaluate the mRNA and protein expression of adhesion molecules. We used 10 μg/mL LPS, a commonly used concentration for inducing inflammation in endothelial cells [ 16 ]. Treatment of bEnd.3 cells with 10 μg/mL LPS significantly increased the levels of ICAM-1, E-selectin, VCAM-1 mRNA, and protein in a time-dependent manner (4–12 h and 12–24 h, respectively) ( Figure 1 a,d).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether chrysin inhibits inflammation, we performed RT-PCR and Western blotting to evaluate the mRNA and protein expression of adhesion molecules. We used 10 μg/mL LPS, a commonly used concentration for inducing inflammation in endothelial cells [ 16 ]. Treatment of bEnd.3 cells with 10 μg/mL LPS significantly increased the levels of ICAM-1, E-selectin, VCAM-1 mRNA, and protein in a time-dependent manner (4–12 h and 12–24 h, respectively) ( Figure 1 a,d).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, arazyme may aggravate the pathogenesis of allergic diseases. However, we elucidated anti-inflammatory effect of arazyme in keratinocytes and endothelial cells (Kim et al, 2013;Kim et al, 2014b). Arazyme has also been shown to effectively alleviate clinical features of atopic dermatitis in an atopic dermatitis-like mouse model.…”
Section: Discussionmentioning
confidence: 98%
“…Arazyme is a metalloprotease that induces anti-inflammatory responses such as downregulation of cytokine and reactive oxygen species (ROS) production (Kim et al, 2013;Kim et al, 2014b). We recently found arazyme to be a useful drug candidate for treatment of atopic dermatitis (Kim et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, TDD also significantly downregulated the production or expression of IL‐6, IL‐1β, MCP‐1 and TNF‐α in LPS‐stimulated EA.hy926 cells in a concentration‐dependent manner. Other studies have reported that ROS also contributed to endothelial adhesion molecule expression and cytokine production . To further validate whether the effect of TDD on the inhibition of inflammation and ROS production in LPS‐stimulated EA.hy926 cells was mediated through HMBOX1, HMBOX1 silencing was conducted.…”
Section: Discussionmentioning
confidence: 99%